Cross-Border Shuttle Trade Indonesia And Egypt: Challenges And Solutions - Irham Amir; Elisa Elisa (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2022)
With the development of technology, it is possible to establish communication with people among countries, with the aim to offer products and services to potential customers abroad. Shuttle trade business is mushrooming among millennials, this is motivated by the desire to take a vacation to a certain destination, so courier service open up opportunities to stay efficient on vacation by performing shuttle trade activity through Whatsapp Group or Instagram. The purpose of the research is to identify challenges and solutions in performing a cross-border shuttle trade business. This study applied action research method and qualitative approaches through in-depth online interview with 30 respondents consisted of travelers, requesters, and candidates of travelers and requesters occupied in Egypt and Indonesia. The result indicates that challenges of the shuttle trade are price competition, packing, platform, and custom clearance. A final solution given is that there must be a competitive price, safety packaging, special and legal platform to perform the shuttle trade activity that can give guarantee over the unexpected situation such as damaged goods, delayed arrival of goods, and goods has not arrived.